The international-migration network - Giorgio Fagiolo; Marina Mastrorillo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2012)
This paper studies international migration from a complex-network perspective. We define the international-migration network (IMN) as the weighted-directed graph where nodes are world countries and links account for the stock of migrants originated in a given country and living in another country at a given point in time. We characterize the binary and weighted architecture of the network and its evolution over time in the period 1960-2000. We find that the IMN is organized around a modular structure characterized by a small-world pattern displaying disassortativity and high clustering, with power-law distributed weighted-network statistics. We also show that a parsimonious gravity model of migration can account for most of observed IMN topological structure. Overall, our results suggest that socio-economic, geographical and political factors are more important than local-network properties in shaping the structure of the IMN.
Keywords: O15; F22; 330; Migration; Complex Networks; International Migration Network; Community Detection; Gravity Models; Internationale Wanderung; Internationale Wirtschaftsbeziehungen; Netzwerk; Welt